A Proposed Mechanism for Trusted Evaluation of Web Services - Aya Joumaa; Basel Hasan; Nasser Nasser (Journal of Engineering and Sustainable Development)
Web services are one of the important innovations in the software field, and they are used on a large scale in modern software systems. Web services have evolved and significantly increased during the last two decades, resulting in large numbers of similar services in terms of function and can be used to perform the same tasks. As a result, choosing the most appropriate web service to meet users' needs has become an important research topic. This research presents a trusted mechanism for evaluating web services by relying on Quality of Service (QoS) metrics, where several metrics that are measurable on the user's side were chosen. Work has been done to make the mechanism general, scalable, and expandable to support additional quality metrics, in addition to focusing on the ease of using this mechanism and the evaluation calculation for the different web services. This research works on ensuring the reliability of the results when sending them by signing results digitally. To prove the possibility of implementing the proposed mechanism, it was tested on three groups of web services, with each group consisting of three functionally similar services. The experiment demonstrated the possibility of implementing the proposed mechanism on different web services.